Phage therapy to inactivate multidrug-resistant P. aeruginosa - Vieira, Anabela Carvalho (2013)
With the increase in antibiotic resistance and after several years of abandonment, the use of bacteriophages (phages), as antimicrobial agents, to destroy bacteria began to arouse interest in the scientific community. This has led to a huge phage research in different fields and currently several studies are ongoing with animals and humans. Pseudomonas aeruginosa is an opportunistic pathogen, which frequently colonizes wounds infections. It has been estimated that a high number of deaths caused by wound infections results of bacterial infection, often by antibiotic-resistant P. aeruginosa. The main target of this work was to explore the potential of phages in controlling multidrug-resistant (MDR) P. aeruginosa strains in vitro and ex vivo (human skin). A new bacteriophages (PA709) was isolated from sewage water samples collected from Hospital Universitário de Coimbra (HUC). A phage suspension (108 PFU mL-1) was obtained using the clinical strain P. aeruginosa 709 as host. After the characterization of the phage candidate, their capacity to lyse other MDR P. aeruginosa clinical isolates from Aveiro, Matosinhos and Coimbra was investigated. The ability of the phage to cause inactivation of P. aeruginosa 709 was evaluated in vitro and in ex vivo (human skin), at 37°C, using a multiplicity of infection (MOI) of 0.5 to 50. In the in vitro assays, the effect of a second dose application, added after 4 hours of incubation, was also tested. The lytic phage PA709 has an icosahedral head with a long contractile tail and a DNA molecule as nucleic acid, a morphology characteristic of members of the Myoviridae family. The phage PA709 show a relatively broad host range (infects 30% of the 51 MDR P. aeruginosa clinical isolates), infecting different genotypes isolated in the three hospitals (Matosinhos, Aveiro and Coimbra). For the best MOI, the number of MDR P. aeruginosa 709 in the human skin in the presence of the phage decreased 4 logs after 2 hours of incubation. The application of a second dose of phage did not increase the efficiency of the therapy. These results show that the phage PA709 was seen to have rapid lytic activity but the number of bacteria gradually increased after that. The occurrence of lysogeny and the development of resistance of the host to the phages could explain the bacterial re-growth. However, no evidence of lysogeny was observed after addition of mitomycin C and no resistant to PA709 phage was detected. In conclusion, phage PA709 presents some interesting features, namely high efficiency in the inactivation of MDR P. aeruginosa , a broad host range and high stability in stock suspensions and in ex vivo human skin. All these attributes make this phage very promising for the treatment of P. aeruginosa skin wound infections. However, more phages should be isolated in the future, for the formulation of cocktails which might improve the inactivation efficiency against P. aeruginosa human skin infections.